Design Thinking Mindset-Is It a Prerequisite for Academic Performance? - Sharma, Santosh Kumar; Padmanabhan NS (International Journal of Social Sciences and Management, 2025)
Academic performance (grades and marks in a subject or course) is the basic indicator of student’s academic success in most of the cases. The available and relevant literature is in line with this proposition. However, there is almost no literature available which can discuss on the academic performance of students from design thinking perspective which has been recognized as a prerequisite for better placement of students in various organizations. Therefore, the present research is novel attempt to examine the empirical relationship between the dimensions of design thinking mindset and academic performance in a sample of 108 students of a premium business school in India. Data has been collected through survey and a validated questionnaire in addition to the marks obtained by the students in a specific subject (indicator of academic performance). By applying appropriate statistical tests, the findings indicate a mixed kind of results. Implications followed by conclusions have been discussed which can motivate future researchers to extend or replicate the present research in different academic or corporate contexts. Int. J. Soc. Sc. Manage. Vol. 12, Issue-2: 104-113.